Endogenous opioid system modulates proximal and distal threat signals in the human brain - Seppälä, Kerttu; Putkinen, Vesa; Harju, Harri; Rebelos, Eleni; Hirvonen, Jussi; Helin, Semi; Rajander, Johan; Karlsson, Henry K.; Saunavaara, Jani; Hyönä, Jukka; Nummenmaa, Lauri (Springer Science and Business Media LLC, 2026)
Fear promotes rapid detection of threats and appropriate fight-or-flight responses. The endogenous opioid system modulates responses to pain and psychological stressors. Fear and anxiety constitute major psychological stressors for humans, yet the contribution of the opioid system to acute human fear remains poorly characterized. We induced intense unconditioned fear in the subjects by gradually exposing them to a living constrictor snake (threat trials) versus an indoor plant (safety trials). Cerebral haemodynamic responses were recorded from 33 subjects during functional magnetic resonance imaging (fMRI). In addition, 15 subjects underwent brain positron emission tomography (PET) imaging using [11C]carfentanil, a high affinity agonist radioligand for μ-opioid receptors (MORs). Pupillary arousal responses to snake and plant exposure were recorded in 36 subjects. Self-reports and pupillometric responses confirmed significant subjective fear and autonomic activation during the threat trials. fMRI data revealed that proximity of the snake engaged brainstem defense circuits, thalamus, dorsal attention network, and motor and premotor cortices. These effects were diminished during repeated exposures. [11C]carfentanil binding to MORs was higher during the fear versus safety condition, and the acute haemodynamic responses to threat were dependent on baseline MOR binding in the cingulate gyrus and thalamus. Finally, baseline MOR tone predicted dampening of the haemodynamic threat responses during the experiment. Preparatory response during acute fear episodes involves a strong motor component in addition to the brainstem responses. These haemodynamic changes are coupled with a deactivation of the opioidergic circuit, highlighting the role of MORs in modulating the human fear response.